Importance of nanophytoplankton biomass during summer 2019 in a retreating marine-terminating glacier-fjord system, Marian Cove, West Antarctica (62°S) - Jeon, Misa; Iriarte, José Luis; Yang, Eun Jin; Park, Jisoo; Alves-de-Souza, Catharina; Park, Sang Jong (Frontiers in Marine Science, 2023)
The biogeochemical dynamics of fjords around Antarctica are strongly influenced by cryospheric, climatic, and oceanographic processes that occur on a seasonal scale. Furthermore, as global climate change continues, there is a growing awareness of the impact of ocean warming on glacier melting, which is expected to affect the composition of phytoplankton community structure in West Antarctica’s nearshore marine areas. In this study, we describe the role of hydrographic forcing on the short-term summer variability of the phytoplankton community in Marian Cove, an Antarctic glacial fjord (62°S). Phytoplankton and hydrographic variables were measured at five stations along the Marian Cove during summer 2019 (January–February). The highest concentrations of microphytoplankton biomass were found in the outer area of the fjord, whereas nanophytoplankton biomass displayed continued dominance during most of the summer period in Marian Cove. Hydrographic assessment showed that freshwater inputs from the glacier influenced the surface layer of the fjord, modulating phytoplankton biomass, which was dominated by nanodiatoms (Minidiscus sp., Thalassiosira spp.) and nanophytoflagellates (Cryptomonas spp., Phaeocystis sp.). Concurrent measurement of phytoplankton biomass and environmental conditions during December 2018–January 2019 indicated that a period of weak southeastern winds generated vertical stability, which led to the development of a major peak of microphytoplankton biomass in the outer cove, driven by warm, allochthonous, oceanic, nutrient-rich waters. High carbon biomass dominated by nanodiatoms and nanophytoflagellates was observed in cold, fresh, and low-light subsurface waters of the cove. Our results highlight the effects of a warming ocean, which may favor the summer resurgence of nanodiatom and nanophytoflagellate communities in Antarctic fjords due to increased glacial meltwater inputs.